The Effectiveness Of Pre-Marital Counseling For Prospective Couples In Enhancing Family Resilience : A Structured Literature Review - Marwah, Andi (Hukum Islam, 2025)
Pre-marital counseling has emerged as an essential tool for fostering strong, resilient marriages by equipping couples with the skills and knowledge needed to address marital challenges. This qualitative study explores the effectiveness of pre-marital counseling, focusing on its impact on communication, conflict resolution, and alignment of shared expectations. Through an in-depth review of case studies and interviews with couples who participated in counseling programs, this research highlights key factors influencing participation, such as accessibility, societal stigma, and awareness.The findings reveal that pre-marital counseling significantly enhances marital satisfaction by improving couples' ability to navigate differences and build mutual understanding. However, barriers such as limited availability of services, financial constraints, and cultural stigmas were identified as significant challenges. Participants emphasized the importance of culturally sensitive and affordable counseling programs, as well as the need for increased public awareness to normalize counseling as a proactive measure.The study concludes that pre-marital counseling is a vital component of marital preparation, contributing to stronger, more stable families. Recommendations include promoting awareness campaigns, implementing policies for mandatory counseling, and enhancing the quality and accessibility of services. These efforts are essential to supporting future couples and ensuring the long-term success of marital relationships.